Slaughter Weight, Carcass Weight, Giblet Percentage, and Abdominal Fat of Broilers Given White Turmeric Extract - Horhoruw, Wiesje Martha; Kewilaa, Arnold Ismael (Sahabat Publikasi, 2024)
White turmeric is an herbal plant that contains additives and has good potential, does not cause residues or is harmful when consumed by livestock. The main components of white turmeric rhizome which have medicinal properties are essential oils and curcuminoids. Curcuminoid compounds have antibacterial properties that can improve the digestive process by killing pathogenic bacteria and stimulating the walls of the gallbladder so that they can facilitate fat metabolism. Administration of white turmeric extract 0%, 2% and 4% had no significant effect on slaughter weight, carcass weight, giblet percentage and abdominal fat percentage of broiler chickens